2013
DOI: 10.1007/s00216-013-7354-7
|View full text |Cite
|
Sign up to set email alerts
|

HRMAS NMR spectroscopy combined with chemometrics as an alternative analytical tool to control cigarette authenticity

Abstract: In this paper, we present for the first time the use of high-resolution magic angle spinning nuclear magnetic resonance (HRMAS NMR) spectroscopy combined with chemometrics as an alternative tool for the characterization of tobacco products from different commercial international brands as well as for the identification of counterfeits. Although cigarette filling is a very complex chemical mixture, we were able to discriminate between dark, bright, and additive-free cigarette blends belonging to six different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The pH of the nicotine environment may results in a single or double nicotine protonation that influences all the hydrogen atoms around the protonated sites, leading to varying chemical shifts. The NMR profiles of cigarette smoke condensate 44 or in EC device 45 may lead to complex NMR profiles difficult to globally interpret, although NMR is used to verify cigarette authenticity 46 . The measured chemical shifts by 1 H NMR clearly showed that the PG + VG e-liquids corresponded to pH 8 whereas PDO generates a more basic environment, equivalent to pH 10.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the nicotine environment may results in a single or double nicotine protonation that influences all the hydrogen atoms around the protonated sites, leading to varying chemical shifts. The NMR profiles of cigarette smoke condensate 44 or in EC device 45 may lead to complex NMR profiles difficult to globally interpret, although NMR is used to verify cigarette authenticity 46 . The measured chemical shifts by 1 H NMR clearly showed that the PG + VG e-liquids corresponded to pH 8 whereas PDO generates a more basic environment, equivalent to pH 10.…”
Section: Discussionmentioning
confidence: 99%